Representasi Visual Orang Utan dalam Laman Taman Nasional Tanjung Puting, Kalimantan Selatan - Murizka, Trinia; Kartika-Ningsih, Harni (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
This paper examines the representation of orang utan species on the official website of a national park. The study aims to explore how orang utans--an endemic species of Indonesia--are represented on web pages accessible to public, particularly those who are interested in visiting Taman Nasional Tanjung Puting (TNTP, or Tanjung Puting National Park in English) in Kalimantan. Employing a multimodal social semiotic framework, the research analyzes a dataset comprising 11 photographs of orang utans featured on TNTP’s official website. A case study method is employed, utilizing Kress and van Leeuwen’s (1996, 2006, 2020) visual grammar framework to examine three strands of meaning: representational, interactional, and compositional. Data were collected by selecting relevant photographs within the site’s gallery followed by analyzing the selected photographs through the lens of visual grammar to reveal the constructed meanings. Findings indicate that TNTP strategically presents a positive representation of orang utans through curated imagery on its official site. TNTP intends to portray orang utans as the central part of TNTP’s conservation agenda and they live in a state of freedom and autonomy strongly protected by TNTP. This representation highlights that orang utans are an important part of the ecosystem whose existence needs to be preserved, respected and protected, not a mere tourist attraction.Keywords - National Park, Orang utan, Social Semiotics, Visual Grammar, Wildlife.